Third Annual Summer Research Summit on Health Equity Organized by the Center of Excellence in Health Equity, Training and Research, Baylor College of Medicine, Houston, Texas 77030, USA on June 9, 2020 - Hamisu M. Salihu, MD, PhD; Deepa Dongarwa, MS; Toi B. Harris, MD (Global Health and Education Projects, Inc., 2020)
This year's summit was unique given the COVID-19 pandemic: a major global outbreak that has imposed severe restrictions in all aspects of our life. At the outset, we were faced with three mutually exclusive options. First option was to cancel the summit in its entirety: this was the easiest and most obvious choice once the COVID-19 pandemic forced a near total lockdown all over the country with unprecedented disruptions of normal daily activities as the disease announced its thunderous touchdown on United States (US) soil. It was also the most-logical response faced with uncertainty regarding summit logistics and expected poor attendance due to the raging pandemic. Second option was to conduct a digital summit restricted to local audiences at Baylor College of Medicine: this option entailed implementing a virtual summit with attendance restricted to participants from our institution only. It sounded like a reasonable choice but that would impede the presence of diversity of topics, perspectives, insights and experiential learning opportunities, which are what render the summit exciting and worth attending. And finally, the last option was to conduct a digital unrestricted summit open to all interested audiences throughout the US. The conduct of a virtual summit open to all participants from around the country was initially considered daunting given the likelihood of amplified technical problems associated with an array of internet access differentials around the country, which would require a strong Information Technology (IT) presence throughout the sessions. Nonetheless, the attractiveness of going national with a virtual summit, despite the pandemic and logistical challenges, slowly gained converts and became the dominant choice. The response and level of participation in this first virtual summit showed an unanticipated surge despite the increase in registration fees to cover IT costs. This year, we had attendees from all regions of the US as well as from the United Kingdom. The range of topics was quite diverse encompassing health disparities in relation to cancers, nutrition, musculo-skeletal disorders, amputation rates, vaccination uptakes and COVID-19 infections. Various solutions were passionately presented to address these disparities including novel health technologies, community engagement and partnerships, improvement in health literacy and alternative therapeutics. There were no hitches despite the complex breakout sessions, and above all, attendees were satisfied and offered outstanding evaluation scores. This was definitely a summit that metamorphosed from pessimism to a triumphant success!   Copyright © 2020 Salihu et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0)which permits unre-stricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.